KEPUASAN KLIEN TERHADAP LAYANAN CYBERCOUNSELING - Arswimba, Bernardinus Agus (Jurnal Bimbingan dan Konseling Borneo, 2022)
Counseling that is usually done so far is face to face, the pandemi has forced counseling to innovate into cybercounseling. Changes that occur will require adaptation. The purpose of this study is to determine client satisfaction with cybercounseling services. This research method uses a mixed method. The majority of client satisfaction with cybercounseling services are very satisfied. The aspect of satisfaction experienced by clients is related to the relationship between the counselor and the client in the cybercounseling process. A comfortable relationship allows clients to tell stories freely without feeling afraid. This data also shows that even though counseling is not done face to face, clients still feel satisfaction in cybercounseling. The media is not an obstacle in the counseling process and this can be overcome if the counselor has the characteristics of a professional counselor, namely: Unconditional Positive Regard, Empathy and Congruence.Keywords : Satisfaction, Clients, Cybercounseling